Characterization of immunoglobulin loci in the gigantic genome of Ambystoma mexicanum - Martinez-Barnetche, Jesús; Godoy-Lozano, Elizabeth Ernestina; Saint Remy-Hernández, Stephanie; Pacheco-Olvera, Diana Laura; Téllez-Sosa, Juan; Valdovinos-Torres, Humberto; Pastelin-Palacios, Rodolfo; Mena, Horacio; Zambrano, Luis; López-Macías, Constantino (Frontiers in Immunology, 2023)
Background The axolotl, Ambystoma mexicanum is a unique biological model for complete tissue regeneration. Is a neotenic endangered species and is highly susceptible to environmental stress, including infectious disease. In contrast to other amphibians, the axolotl is particularly vulnerable to certain viral infections. Like other salamanders, the axolotl genome is one of the largest (32 Gb) and the impact of genome size on Ig loci architecture is unknown. To better understand the immune response in axolotl, we aimed to characterize the immunoglobulin loci of A. mexicanum and compare it with other model vertebrates. Methods The most recently published genome sequence of A. mexicanum (V6) was used for alignment-based annotation and manual curation using previously described axolotl Ig sequences or reference sequences from other vertebrates. Gene models were further curated using A. mexicanum spleen RNA-seq data. Human, Xenopus tropicalis, Danio rerio (zebrafish), and eight tetrapod reference genomes were used for comparison. Results Canonical A. mexicanum heavy chain (IGH), lambda (IGL), sigma (IGS), and the putative surrogate light chain (SLC) loci were identified. No kappa locus was found. More than half of the IGHV genes and the IGHF gene are pseudogenes and there is no clan I IGHV genes. Although the IGH locus size is proportional to genome size, we found local size restriction in the IGHM gene and the V gene intergenic distances. In addition, there were V genes with abnormally large V-intron sizes, which correlated with loss of gene functionality. Conclusion The A. mexicanum immunoglobulin loci share the same general genome architecture as most studied tetrapods. Consistent with its large genome, Ig loci are larger; however, local size restrictions indicate evolutionary constraints likely to be imposed by high transcriptional demand of certain Ig genes, as well as the V(D)J recombination over very long genomic distance ranges. The A. mexicanum has undergone an extensive process of Ig gene loss which partially explains a reduced potential repertoire diversity that may contribute to its impaired antibody response.